2010
DOI: 10.1677/jme-09-0176
|View full text |Cite
|
Sign up to set email alerts
|

Acute food deprivation reduces expression of diazepam-binding inhibitor, the precursor of the anorexigenic octadecaneuropeptide ODN, in mouse glial cells

Abstract: In the central nervous system of mammals, the gene encoding diazepam-binding inhibitor (DBI) is exclusively expressed in glial cells. Previous studies have shown that central administration of a DBI processing product, the octadecaneuropeptide ODN, causes a marked inhibition of food consumption in rodents. Paradoxically, however, the effect of food restriction on DBI gene expression has never been investigated. Here, we show that in mice, acute fasting dramatically reduces DBI mRNA levels in the hypothalamus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Although, DBI mRNA and immunoreactivity has been found both in neurons and astrocytes (Alho et al, 1985, 1989; Tonon et al, 1990; Bouyakdan et al, 2015), DBI is mainly expressed in non-neuronal cells, such as ependymocytes, tanycytes, and proteoplasmic astrocytes (Tong et al, 1991; Lanfray et al, 2013; Bouyakdan et al, 2015). Consistent with a role of glial endozepines as anorexigenic factors, food deprivation reduces the mRNA expression of DBI in ependymocytes bordering the third and lateral ventricle as well as in median eminence tanycytes and arcuate protoplasmic astrocytes (Compère et al, 2010; Lanfray et al, 2013). The impact of endozepine signaling on neuronal populations involved in food intake control has been evaluated, with a focus on the hypothalamic leptin-sensitive neurons.…”
Section: Introductionmentioning
confidence: 67%
“…Although, DBI mRNA and immunoreactivity has been found both in neurons and astrocytes (Alho et al, 1985, 1989; Tonon et al, 1990; Bouyakdan et al, 2015), DBI is mainly expressed in non-neuronal cells, such as ependymocytes, tanycytes, and proteoplasmic astrocytes (Tong et al, 1991; Lanfray et al, 2013; Bouyakdan et al, 2015). Consistent with a role of glial endozepines as anorexigenic factors, food deprivation reduces the mRNA expression of DBI in ependymocytes bordering the third and lateral ventricle as well as in median eminence tanycytes and arcuate protoplasmic astrocytes (Compère et al, 2010; Lanfray et al, 2013). The impact of endozepine signaling on neuronal populations involved in food intake control has been evaluated, with a focus on the hypothalamic leptin-sensitive neurons.…”
Section: Introductionmentioning
confidence: 67%
“…Dbi binds GABA(A) receptors with high affinity [42], [43], and it is thought that suppression of GABAergic signaling is one mechanism through which Dbi modulates retinal neurotransmission, particularly in the inner plexiform layer [40], [41], [44], which further increases following activity-dependent phosphorylation [45], which is a hallmark of diabetes-related retinal pathology [46]. Combined with previous reports of insulin-mediated regulation of Dbi expression [47], [48], the responsiveness of Dbi protein and mRNA to insulin therapy in the present study suggests that this target may be a promising candidate for treatments focused on modulating neurovascular function in the diabetic retina.…”
Section: Discussionmentioning
confidence: 89%
“…Consistent with this observation, behavioral studies have shown that intracerebroventricular (ICV) injection of ODN and its C-terminal octapeptide (OP) fragment attenuates food consumption in rodents (Garcia de mateos-Verchere et al 2001;Do Rego et al 2007;Compère et al 2010). It has been found also that the inhibitory effect of ODN on food intake is suppressed by treatment with an antagonist of the metabotropic endozepine receptor, cyclo 1-8 [DLeu 5 ]OP (cDLOP), suggesting that the anorexigenic action of ODN is mediated via a G-protein-coupled receptor-signaling pathway but not through central-type or peripheral-type benzodiazepine receptors (Do Rego et al 2007).…”
Section: Introductionmentioning
confidence: 74%